Preliminary Characterisation of Lowland and Upland Rice from Sarawak, Malaysian Borneo - Zazevia, Frank Clifton; Freddy Yeo, Kuok San; Renee Priscilla Trawas, Sylvester Embuas; Meekiong, Kalu; Zinnirah, Shabdin; Lai, Lee San (UNIMAS Publisher, 2024)
Oryza sativa L. or commonly known as rice belongs to the family of Poaceae. In Malaysia, rice is normally cultivated either as lowland or upland rice. Sarawak is a state with diverse types of rice. All Sarawak rice are landraces. Despite the fact that Sarawak is rich in rice biodiversity, the assessment of the morphological traits which may provide basic information that is useful for the future breeding programs is still unavailable. The nomenclature of the landraces is based on the name given by the farmers. Problems arise when landraces having the same morphological characteristics were given different names and vice versa. In addition, the purity of seeds is unreliable. Common practices by the local farmers such as planting different rice landraces in the same field either in one plot or in different plots but very near to each other has contributed to the impurity of the seeds. The present study was undertaken with the objective to characterise the morphological traits of 22 lowland and 22 upland rice accessions from the North-Western region of Sarawak. The morphological traits observed on the 44 rice accessions viz., blade colour, ligule shape, ligule colour, auricle colour, heading days, flowering days, panicle type, culm length, panicle number, number of filled grain, seed length and grain colour exhibited variations. There are variations which may be considered in future Sarawak rice breeding programs.